SCOPE of Open Education: A New Framework for Research - Clinton-Lisell, Virginia Elizabeth; Roberts-Crews, Jasmine; Gwozdz, Lindsey (International Review of Research in Open and Distributed Learning, 2023)
The field of open education and research on the topic has notably expanded since the introduction of the term 20 years ago. Given these developments, a framework to structure research inquiry is necessary to ground and organize findings in open education. We propose the SCOPE framework for open education research: social justice, cost, outcomes, perceptions, and engagement. In this article, we explain how this framework emphasizes the need for social justice at the forefront of open education research. In addition, we incorporate existing theories in social justice, motivation, cognition, pedagogy, and engagement into each of the components to propose theoretical connections to future open education research. We suggest areas in which future research is needed. Finally, we conclude with suggestions as to how the SCOPE framework may be useful when connecting open education to open science and open scholarship as well as a call for considering intersectionality and critical methods in quantitative research (QuantCrit) in future inquiry.